2019
DOI: 10.1016/j.appet.2019.104374
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ attachment representations and infant feeding practices

Abstract: This study examined how fathers' adult attachment representations, assessed before the birth of their first child, predict feeding practices with their 8-month-old infants. Fathers have been underrepresented in child feeding research, particularly in longitudinal and observational studies. Feeding is a key parenting task of infancy and a growing number of studies have begun to explore the connection between attachment and parental feeding practices and behavior, revealing a clear link between mothers' adult at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 70 publications
1
28
0
1
Order By: Relevance
“…In these studies, full‐time employment, 50,53 lower educational status, 50 and lower perceived responsibility for feeding children 84 is linked with fathers' use of more controlling feeding strategies. One longitudinal study found that more secure father attachment assessed prenatally predicts greater responsive feeding practices with their 8‐month‐old infant 85 . Finally, a minority of studies examined the interplay between mothers and fathers in the context of food parenting.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, full‐time employment, 50,53 lower educational status, 50 and lower perceived responsibility for feeding children 84 is linked with fathers' use of more controlling feeding strategies. One longitudinal study found that more secure father attachment assessed prenatally predicts greater responsive feeding practices with their 8‐month‐old infant 85 . Finally, a minority of studies examined the interplay between mothers and fathers in the context of food parenting.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies were conducted in the USA ( n = 20), 24–43 followed by Australia ( n = 10), 44–53 United Kingdom ( n = 8), 54–61 New Zealand ( n = 1), 62 Norway ( n = 2), 63,64 and Sweden ( n = 1) 65 . Thirty‐four studies, reported in 33 papers, employed a quantitative design, including RCTs of an intervention ( n = 5), 32,39,50,62,63 observational cohort studies ( n = 8), 24,27–29,35,54,59,60 cross‐sectional studies ( n = 11), 24,30,38,41–44,46,48,53,64 a case–control study, 26 a within‐subject experimental study, 40 a quasi‐experimental study, 51 and observational descriptive/measurement development 31 . Six studies undertook secondary analyses; two used cross‐sectional data, 25,37 two studies used data from observational cohort studies, 33,45 one used control group data, 34 and one used data from an RCT 36 .…”
Section: Resultsmentioning
confidence: 99%
“…The quantitative non‐randomised studies all included participants who were representative of the target population 28,30,31,40,41,51 . The quantitative descriptive studies were generally well conducted although it was not always possible to ascertain sample representativeness 26,27,29,33,34,37,38,44,45,48,53,59,60,64 . Some of the quantitative descriptive studies focused on participants from particular groups such as infants who had been adopted, 33 and as such, these findings are not generalizable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the relevant literature, studies done with fathers are limited and those that recruited fathers generally focused on well-educated fathers and growing level of responsibility for children's eating and feeding practices was explained to be correlated with education. [37][38][39][40] However; there is no study that investigates effects of fathers, their age, education level and other demographic characteristics upon maternal feeding practices and decisions.…”
Section: Discussionmentioning
confidence: 99%